2002
DOI: 10.1038/nri843
|View full text |Cite
|
Sign up to set email alerts
|

The immunobiology of schistosomiasis

Abstract: Schistosomes are parasitic worms that are a prime example of a complex multicellular pathogen that flourishes in the human host despite the development of a pronounced immune response. Understanding how the immune system deals with such pathogens is a daunting challenge. The past decade has seen the use of a wide range of new approaches to determine the nature and function of the immune response to schistosomes. Here, we attempt to summarize advances in our understanding of the immunology of schistosomiasis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
1,184
4
22

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,050 publications
(1,247 citation statements)
references
References 144 publications
37
1,184
4
22
Order By: Relevance
“…This result could explain the observed decrease in the size of granulomas because Th2 cells are often the main lymphocyte population in this structure. 31 In agreement with the decrease of the Th2 skewed population after DNA treatment (Figure 2), we observed a decrease in IL-4 and IL-13 production in lungs of mice treated with DNA accompanied by increased production of IL-12 and IFN-␥ (Figure 4), as well as increased expression of mRNA for IFN-␥ and IL-12 ( Figure 3). In previous work, using a TB model that classically induces a Th1 pattern, mice immunized with DNAhsp65 showed increases of protective cytokines, IFN-␥ and IL-12.…”
Section: Discussionsupporting
confidence: 86%
“…This result could explain the observed decrease in the size of granulomas because Th2 cells are often the main lymphocyte population in this structure. 31 In agreement with the decrease of the Th2 skewed population after DNA treatment (Figure 2), we observed a decrease in IL-4 and IL-13 production in lungs of mice treated with DNA accompanied by increased production of IL-12 and IFN-␥ (Figure 4), as well as increased expression of mRNA for IFN-␥ and IL-12 ( Figure 3). In previous work, using a TB model that classically induces a Th1 pattern, mice immunized with DNAhsp65 showed increases of protective cytokines, IFN-␥ and IL-12.…”
Section: Discussionsupporting
confidence: 86%
“…FREP14 is different from known FREPs in that it is encoded by a single locus and is not upregulated in early or late stage S. mansoni exposure, but is upregulated in late stage E. paraensei infection. Furthermore, gene expression during the snail's ontogenesis and at a late stage of trematode-infection (52 dpe) has been investigated in the two newly-identified genes (FReM and FREP14) described in this paper and five representative members of known FREPs (FREPs 2,3,4,12,and 13). A variety of expression patterns were observed, suggestive of functional diversity among the members of FBG-bearing proteins.…”
mentioning
confidence: 93%
“…The morbidity in Schistosoma mansoni infections arises from the granulomatous, immune-mediated response to eggs that become trapped in the host liver and gut after being released by fecund females residing in the venous system of the liver [1]. Immunological studies of the adaptive immune response in the mouse have focused on the prevalent CD4 + T cell activity and revealed that, initially, the host develops a Th1 response, which is characterized by the production of IFN-c.…”
Section: Introductionmentioning
confidence: 99%
“…However, in vivo investigations with S. mansoni have still to clarify the role of the innate immune system in priming either the initial Th1 response or the successive Th2 response that drives the main pathological changes in the liver and gut [1]. Therefore, the basic interest in this study was to resolve whether MyD88 is involved in the pathogenesis, especially the granuloma formation, in schistosomiasis and, furthermore, whether MyD88 influences the quality of the subsequent adaptive immune responses raised against this helminth.…”
Section: Introductionmentioning
confidence: 99%